(untitled) (Journal of Global Arts Studies, 2024)
Background: Amid the rapid development of globalization and informatization, traditional cultural elements are experiencing renewed vitality within modern design practices. The persimmon pedicle pattern, as a traditional decorative motif rich in cultural symbolism, has become an important bridge connecting traditional culture with contemporary aesthetics through its innovative applications in modern design. Objective: This study aims to explore the application of the persimmon pedicle pattern in modern cultural and creative products, examining its functions in cultural communication and emotional connection. The research seeks to reveal how innovative expressions through visual elements and design language contribute to the inheritance and promotion of traditional culture. Methods: Through literature review and case study analysis, this study outlines the historical and cultural connotations of the persimmon pedicle pattern and analyzes its applications across different categories of cultural and creative products. The research focuses particularly on its innovative expressions in visual elements and design language. Results: The findings indicate that the application of the persimmon pedicle pattern in cultural and creative products not only enhances cultural identity and emotional resonance but also demonstrates unique educational value and expressive potential. This allows traditional cultural symbols to regain vitality and relevance within contemporary consumer culture. Conclusion: By integrating traditional decorative motifs with modern design concepts and adopting innovative expressions in visual elements and design language, the innovative inheritance and dissemination of traditional culture can be effectively promoted. The study provides new perspectives and creative directions for contemporary cultural and creative design.